Recording Analysis - Moylan, William (Focal Press, 2020)
Recording Analysis: How the Record Shapes the Song identifies and explains how the sounds imparted by recording processes enhance the artistry and expression of recorded songs. Moylan investigates how the process of recording a song transforms it into a richer experience and articulates how the unique elements of recorded sound provide essential substance and expression to recorded music. This book explores a broad array of records, evaluating the music, lyrics, social context, literary content and meaning, and offers detailed analyses of recording elements as they appear in a wide variety of tracks. Accompanied by a range of online resources, Recording Analysis is an essential read for students and academics, as well as practitioners, in the fields of record production, song-writing and popular music.